Interpretation Of Ultrasound Image - Islam, Md. Saidul; Mostafa, Md. Gulam (KYAMC Journal, 2013)
An ultrasound system constructs an image by a series of sound waves produced by its transducer elements from different tissues at different depths of the body. Normal B (Brightness) mode Ultrasonography displays an image at grey scales from bright to black according to the tissue characters and nature of sound wave transmission. M(Motion) mode produced a wavy line taking B-mode waves which is applicable in moving structure like heart.Doppler sonography is a special technique to evaluate blood flow through a blood vessel using Doppler shift equation. Color Doppler uses for direction and speed of blood flow, where as, power Doppler can detect even a very low flow state of a blood vessel. Combined uses of B-mode and color denotes either Duplex or Triplex sonography according to numbe of images used. KYAMC Journal Vol. 3, No.-2, January 2013, Page 301-305 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15172